Oxidant-free oxidative gold catalysis: the new paradigm in cross-coupling reactions - Akram, Manjur O.; Banerjee, Somsuvra; Saswade, Sagar S.; Bedi, Vaibhav; Patil, Nitin T. (Chemical Communications, 2018)
The construction of C-C and C-X (X = hetero atom) bonds is the core aspect for the assembly of molecules. In this regard, late transition-metal-catalyzed cross-coupling reactions have retained their dominance for decades. Lately, gold catalysts have been emerging as a reliable contender for such transformations owing to the recent findings that reveal gold's potential beyond carbophilic -Lewis acid. The newfound ability of gold to undergo redox transformations under certain circumstances has allowed us to explore gold catalysts as a viable alternative to other late transition-metals for efficient construction of cross-coupled products. This feature article critically presents an overview of all the redox neutral cross-coupling reactions enabled by gold catalysis, which we believe would stimulate further research activities in this promising area.

Ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox relay catalysis - Sancheti, Shashank P.; Akram, Manjur O.; Roy, Rupam; Bedi, Vaibhav; Kundu, Shubhankar; Patil, Nitin T. (Chemistry-An Asian Journal, 2019)
Reported herein is an ortho-oxygenative 1,2-difunctionalization of diarylalkynes under merged gold/organophotoredox catalysis to access highly functionalized 2-(2-hydroxyaryl)-2-alkoxy-1-arylethan-1-ones. Detailed mechanistic studies suggested a relay process, initiating with gold-catalyzed hydroalkoxylation of alkynes, to generate enol-ether followed by a key formal [4+2]-cycloaddition reaction. The successful application of the present methodology was also shown for the synthesis of benzofurans.
Keywords: binary catalyst system; Gold catalysis; organocatalyst; photoredox; synthetic methodology